The Effect of Korean Celebrity Endorsement on Perceived Product Quality and Brand Loyalty: Case of Indonesian Skincare Brand in DKI Jakarta - Aisyah Safira Putri; Dr. Leonnard Ong; Sasotya Pratama (Sekolah Tinggi Manajemen IPMI, 2023)
According to Indonesian Cosmetic Association, the beauty industry in Indonesia has rapidly increased as the number of brands varied. To attract more customers, many local brands adopt a celebrity endorsement strategy with Korean stars. In recent years’ Korean celebrity endorsement has brought the eye of the public and has benefited businesses in increasing the awareness from fans and sometimes even selling out. However, it becomes a concern whether this strategy can bring the intended result and bring actual buying behavior. The purpose of this research is to examine the impact of celebrity endorsement on perceived product quality and brand loyalty among 100 young-adult women exposed to Somethinc skincare brand and NCT who have previously purchased the product in DKI Jakarta. This study uses quantitative analysis with Partial Least Square Equation Modeling (PLS-SEM) to analyze the data. The result of this study shows that Celebrity Endorsement shows a positive relationship with Perceived Product Quality. AndPerceived Product Quality positively affects Brand Loyalty. This study provides empirical evidence that the above-mentioned relationships do exist, and companies can strategically leverage the facts to their advantage and drive customer perceptions of quality and loyalty through the promotion of appropriate celebrity endorsements.